Las necesidades de información de los investigadores del área de Humanidades y Ciencias Sociales - Calva-gonzález, Juan José (Revista General de Información y Documentación, 2003)
Research was carried out to ascertain the information needs of researchers in the field of the humanities and social sciences. The relation or influence due to the stage of the research, its nature, the category of the researcher and his kinds of information needs were also investigated. A survey was carried out with full-time researchers working at the Institutes of Humanities and Social Sciences of the National Autonomous University of Mexico (UNAM). Results indicated that their information needs are concrete, on a given theme or problem, or about an author. It was also found that the variables evaluated have no significant influence on the types of information needs.